Analyse harmonique de réseaux électriques : étude de cas - DELASSI YOUCEF; BOULAHIA AHMED; Mahi, Djilali (Université Amar Telidji de Laghouat Faculté des Sciences et Technologie; Département Électrotechnique, 2024)
Non-linear residential, commercial and industrial loads connected to the electrical power distribution network draw non-sinusoidal currents. These currents, crossing the connections (lines, transformers) cause the appearance of non-sinusoidal voltages in the network; causing in turn non sinusoidal currents, often to the inconvenience of the rest of the connected loads. Indeed, current and voltage harmonics alter the operation of the electrical equipment and reduce the performance of the network. The quality of the wave thus becomes a requirement to be respected by both the electricity distributor and the consumer. It is necessary to limit the propagation of current harmonics and to reduce the deformations of network voltages. The objective of this work is to evaluate current and voltage harmonics caused by nonlinear loads and to propose methods to counter their propagation and thus achieve the reduction of voltage harmonics. The study concerns the harmonic analysis of a distribution network. We used ETAP 19.5 (Power System Harmonic Analysis) software to model and simulate the power grid. The method of placing shunt capacitors of appropriate size at strategic locations in the network was used as an optimization technique. It has improved the power factor, reducing losses and voltage drops.
Electrotechnique industrielle